Efficacy and Safety of Liraglutide in Adolescents Aged 12–15 Years with Obesity: a Prospective 24-week Observational - Olga P. Kovtun; Margarita A. Ustiuzhanina; Svyatoslav I. Solodushkin; Lyudmila V. Kovalchuk; Kira Ya. Zaslavskaya (Педиатрическая фармакология, 2025)
Background. The problem of childhood obesity remains relevant for modern healthcare. Effective treatment models for this disease are needed with the inclusion of new therapeutic agents, including GLP-1 receptor agonists such as liraglutide (approved from the age of 12). However, its safety and efficacy in pediatrics have not yet been sufficiently studied and require further research.The aim of the study is to evaluate the efficacy and safety of the GLP-1 receptor agonist liraglutide, a solution for subcutaneous administration in pediatric practice for body weight correction in children with obesity aged 12–15 years in combination with a personalized diet and increased physical activity.Methods. The cohort study conducted on the basis of Children’s City Hospital No. 11 (Yekaterinburg) from March to October 2024 included children aged 12–15 years with an exogenously constitutional form of obesity (SDS BMI ≥ 2.0) with confirmed ineffectiveness of lifestyle correction for more than a year. The follow-up period was 24 weeks and included 9 visits. The main criterion of effectiveness is the change in SDS BMI by the 24th week. Safety was assessed by the frequency and severity of adverse events, as well as by the effect on linear growth.Results. The children of the study groups were comparable in all characteristics (p > 0.05). The main group was prescribed liraglutide — an analog of GLP-1— at a dose of 3.0 mg subcutaneously daily. During the first month, the dose was titrated to the maximum according to the instructions, then the drug was used for another 20 weeks. At week 24, a significant decrease in SDS BMI was recorded in the main group compared with the control (therapeutic effect): –0.343 (95% CI: –0.501 to –0.185), p < 0.001.Conclusion. The results obtained confirm the potential of usage of the liraglutide as part of complex therapy in adolescents with obesity and substantiate the expediency of its further study in pediatric practice.